SYNTHESIS, CHARACTERIZATION, THEORETICAL TREATMENT AND ANTIMICROBIAL ACTIVITY STUDIES OF SOME METAL IONS COMPLEXES WITH 2-HYDROXY-4-NITRO PHENYL PIPERONALIDENE - Yousif, I Q; Alias, M F (Al-Nahrain Journal of Science, 2010)
ions V(IV), Co(II), Rh(III), Pd(II), Cu(II) and Cd(II) were prepared in ethanolic medium. Theprepared complexes were characterized by FT-IR, Uv-Vis spectroscopy, metal analysis, magneticsusceptibility and conductivity measurements. The nature of the complexes formed in ethanolicsolution was studied following the molar ratio method. From the spectral studies, monomerstructures for the V(IV), Co(II) and Cd(II) complexes and dimeric structures for the othercomplexes were proposed. The proposed geometry for prepared complexes was Ochtahedral forCo(II) and Rh(III) complexes, square planer for Pd(II) and Cu(II) complexes, square pyramidal forV(IV) complex and tetrahedral for Cd(II) complex. Structural geometries of these compounds werealso suggested in gas phase by using Hyper Chem-8 program for the molecular mechanics andsemi-empirical calculations. The Hf and Eb for the prepared compounds were calculated byusing PM3 method. Also PM3 was used to evaluate the vibration spectra for the Schiff base andstarting material. Preliminary in vitro tests for antimicrobial activity shows that most of theprepared compounds display good activity to (S. aureus), (E. coli) and (C.albicans).